Beyond criminal punishment: A dialogue between restorative justice and some transition scenarios in Colombia (2019)
This article is the result of a research project that proposes a dialogue between Transitional Justice (JT) and Restorative Justice (JR) in Colombia. We explore the articulation and tensions between the two models from a multidisciplinary perspective in which legal anthropology and critical theories of law intersect. Our approach is threefold and explores the issue from conceptual, empirical, and legal perspectives. Making use of an ethnographic methodology and qualitative social research techniques, we address different contexts intertwined by the same unit of analysis, namely, experiences and restorative processes in political transition scenarios, related to the implementation of Law 975 of 2005 and the implementation of the La Habana peace agreements. © 2019, Universidad Nacional de Colombia. All rights reserved.